Size and deformability based separation of circulating tumor cells from castrate resistant prostate cancer patients using resettable cell traps. Issue 10 (21st May 2015) - Qin, Xi; Park, Sunyoung; Duffy, Simon P.; Matthews, Kerryn; Ang, Richard R.; Todenhöfer, Tilman; Abdi, Hamid; Azad, Arun; Bazov, Jenny; Chi, Kim N.; Black, Peter C.; Ma, Hongshen
<x xml:space="preserve">Abstract</x> Separation of CTCs using resettable cell traps followed by single-cell spectral analysis.